Comparative Genomic Analyses Provide New Insights into the Evolutionary Dynamics of Heterochromatin in Drosophila. - Ruggiero Caizzi; Roberta Moschetti; Lucia Piacentini; Laura Fanti; Renè Massimiliano Marsano; Patrizio Dimitri (PLoS Genetics)
The term heterochromatin has been long considered synonymous with gene silencing, but it is now clear that the presence of transcribed genes embedded in pericentromeric heterochromatin is a conserved feature in the evolution of eukaryotic genomes. Several studies have addressed the epigenetic changes that enable the expression of genes in pericentric heterochromatin, yet little is known about the evolutionary processes through which this has occurred. By combining genome annotation analysis and high-resolution cytology, we have identified and mapped 53 orthologs of D. melanogaster heterochromatic genes in the genomes of two evolutionarily distant species, D. pseudoobscura and D. virilis. Our results show that the orthologs of the D. melanogaster heterochromatic genes are clustered at three main genomic regions in D. virilis and D. pseudoobscura. In D. virilis, the clusters lie in the middle of euchromatin, while those in D. pseudoobscura are located in the proximal portion of the chromosome arms. Some orthologs map to the corresponding Muller C element in D. pseudoobscura and D. virilis, while others localize on the Muller B element, suggesting that chromosomal rearrangements that have been instrumental in the fusion of two separate elements involved the progenitors of genes currently located in D. melanogaster heterochromatin. These results demonstrate an evolutionary repositioning of gene clusters from ancestral locations in euchromatin to the pericentromeric heterochromatin of descendent D. melanogaster chromosomes. Remarkably, in both D. virilis and D. pseudoobscura the gene clusters show a conserved association with the HP1a protein, one of the most highly evolutionarily conserved epigenetic marks. In light of these results, we suggest a new scenario whereby ancestral HP1-like proteins (and possibly other epigenetic marks) may have contributed to the evolutionary repositioning of gene clusters into heterochromatin.